2020
DOI: 10.1002/bdm.2162
|View full text |Cite
|
Sign up to set email alerts
|

Rivals without a cause? Relative performance feedback creates destructive competition despite aligned incentives

Abstract: Whether people compete or cooperate with each other has consequences for their own performance and that of organizations. To explain why people compete or cooperate, previous research has focused on two main factors: situational outcome structures and personality types. Here, we propose that—above and beyond these two factors—situational cues, such as the format in which people receive feedback, strongly affect whether they act competitively, cooperatively, or individualistically. Results of a laboratory exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…Furthermore, although past research has identified a positive relation between competition and academic cheating (Whitley, 1998) and found that competition can increase unethical behaviors (e.g., Moran & Schweitzer, 2008; Vriend et al, 2016), we found no effect of incentives to compete on cheating rates. Although participants knew that there was an incentive to perform better than everyone else, they did not receive direct feedback on their own performance or their ranking within the school (Garcia, Tor, & Gonzalez, 2006; Woike & Hafenbrädl, 2020). Future studies could investigate the effects of rank feedback on cheating in adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although past research has identified a positive relation between competition and academic cheating (Whitley, 1998) and found that competition can increase unethical behaviors (e.g., Moran & Schweitzer, 2008; Vriend et al, 2016), we found no effect of incentives to compete on cheating rates. Although participants knew that there was an incentive to perform better than everyone else, they did not receive direct feedback on their own performance or their ranking within the school (Garcia, Tor, & Gonzalez, 2006; Woike & Hafenbrädl, 2020). Future studies could investigate the effects of rank feedback on cheating in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Social comparisons of one's own achievement with that of others can lead to increased competition (Garcia, Tor, & Schiff, 2013). Past research has shown that envy for other's achievements can lead to deception in negotiations (Moran & Schweitzer, 2008) and that situational factors like ranking systems can increase unethical behaviors (Vriend et al, 2016), lead to destructive competition (Hafenbrädl & Woike, 2018), sabotage of others' work (Charness et al, 2014), and lower rates of cooperation (Woike & Hafenbrädl, 2020). In academic contexts, a meta-analysis identified a positive relationship between perceived competition for grades and cheating in college students (Whitley, 1998).…”
Section: Studymentioning
confidence: 99%
“…In fact, the effect of comparative evaluation on zero-sum beliefs emerged even when controlling for rankings included in a performance report (Chambers & Baker, 2020; Woike & Hafenbrädl, 2020). This finding highlights the impact of managerial communications that occur between employees and their supervisors.…”
Section: Discussionmentioning
confidence: 97%
“…In Study 2, we examined whether the effect of comparative evaluation emerged over and above another factor that has been discussed in the literature to increase zero-sum beliefs: rankings (Chambers & Baker, 2020; Woike & Hafenbrädl, 2020). We manipulated rankings independent of comparative evaluation (thus yielding a 2 × 2), and the rankings served as our feedback valence manipulation.…”
Section: Studymentioning
confidence: 99%
“…Although for a long time the received wisdom was that competition does not exist in planned economies, new case studies can contribute much to the discussion about the impact of competition and cooperation within a business organization on the performance of the planned economy in which it operates. 88 It is now clear that in the Soviet system, it was not only enterprises that competed for resources; so too did ministries and departments representing political groups of influence. The clash of interests between these groups caused ambitious projects to fail.…”
Section: The Business History Of Russia As An Alternative Business Hi...mentioning
confidence: 99%